Biofilm Formation by Protues Mirabilis Isolated From Patients Suffering From Urinary Tract Infections in Baqubah City - Shaymaa Majeed AL–Dahlaki (Academic Science Journal)
Protues mirabilis has the ability to induce urinary tract infections primarily has to do with the formation of biofilms on catheter and UTI surfaces. This bacteria expresses a number of virulence factors essential to the creation of biofilms. Fifty urine specimens were taken from patients who were hospitalized and under treatment from the clinical laboratories of Baquba Teaching Hospital. Of those fifty specimens, fifteen clinical specimens were positive for isolates of Protues mirabilis. The results showed that all the P. mirabilis isolates under study were 100% resistant to the Gentamicin, Cefotaxime and the resistance of the isolates to Vancomysin and Azithromycin were 90%, Cefixime, Augmentin by 80%, and their resistance to Piperacillin-tazobactam by 70%. According to these percentages, the isolates were divided into two classes Extensively Drug Resistance (XDR) (90%), which were resistant to the seven antibiotics that were used in the study, and (10%) were Multi Drug Resistance (MDR) which were resistant to four antibiotic. Results showed that the P. mirabilis have the ability to produce biofilm, all isolates could produce biofilm but in deferent percentage 70% were strong ,30% were moderate, and the absorbency value was ranged from (0.353 – 0.159). The convention PCR analysis revealed that the gene (Esp), encoding the enzymes that cause Proteus mirabilis to form biofilm, accounted for 15 (40%) of the total.